Impact of Zakat Distribution on Entrepreneurship Program: A Case of BAZNAS Yogyakarta, Indonesia - Sutrisno Sutrisno; Razali Haron; Yogi Gusana Saputra (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2022)
This study aims to determine and analyze the impact of the Entrepreneurship program on the level of the material and spiritual welfare of mustahik households before and after receiving zakat funds with the CIBEST model. Moreover, this study uses descriptive quantitative research methods. The sample used is 36 respondents of zakat recipients in BAZNAS Yogyakarta City with a non-probability sampling technique. This study used a questionnaire to collect data. Furthermore, data analysis used is a t-test and CIBEST model. The results of the measurement through the t-test on the material and the spiritual variable were significant differences in the level of welfare of mustahik households before and after receiving zakat assistance. The average income of mustahik after receiving zakat assistance is increased to 26,3 percent. Moreover, based on the CIBEST model, there is a change in the spiritual and material level of mustahik after receiving zakat assistance. After receiving the zakat fund, the number of mustahik households increased in the prosperous category (quadrant I) by 22.2 percent. The poor spiritual category (quadrant II) decreased by 19.44 percent. Thus, entrepreneurship programs can improve the welfare of zakat recipients in BAZNAS Yogyakarta city.